2019
DOI: 10.35940/ijrte.b2158.078219
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of StormPav Green Pavement System with Storm Water Management Model and InfoWorks Collection System

Abstract:  Abstract: Prior to any construction work related to stormwater, it is preferable to involve a computer-based modelling. This paper outlines two different computer-based modelling tools to model a green technology named StormPav Green Pavement. In determining befitting software for use, two key factors are considered: (i) fast model construction (ii) provision of an affordable design model. To meet these key factors, the Storm Water Management Model (SWMM), and InfoWorks Collection System (CS) are deployed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…One of the stormwater control measures that suitable for a road is a permeable road. Its general structure consisted of a top layer of permeable pavement allowing water to seep through and a bottom layer of storage facility allowing water to be stored temporarily under the road [9]. The outflow of the storage layer was through a 50 mm diameter orifice.…”
Section: Permeable Roadmentioning
confidence: 99%
“…One of the stormwater control measures that suitable for a road is a permeable road. Its general structure consisted of a top layer of permeable pavement allowing water to seep through and a bottom layer of storage facility allowing water to be stored temporarily under the road [9]. The outflow of the storage layer was through a 50 mm diameter orifice.…”
Section: Permeable Roadmentioning
confidence: 99%
“…These past studies [7][8][9][10][11] have been verified numerically based on water balance; however, these studies have not been validated due to the absent of a StormPav system in the field. As such, the R&D team has set up an actual-scaled StormPav system in a residential setting in Figure 3.…”
Section: Field Testmentioning
confidence: 99%
“…There are also other studies [9][10][11] that represent StormPav system using the "conduit" in SWMM5. Authors reported that StormPav could convey water via its middle layer and a closed rectangular "conduit" is best to represent the system.…”
Section: Introductionmentioning
confidence: 99%